2022
DOI: 10.3390/biomedicines10030611
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transcriptome Profiling Unveils Novel Deregulated Gene Signatures Involved in Pathogenesis of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder that is characterized by a progressive loss of cognitive functions at a higher level than normal aging. Although the apolipoprotein (APOE) gene is a major risk factor in developing AD, other genes have also been reported to be linked with complex phenotypes. Therefore, this genome-wide expression study explored differentially expressed genes as possible novel biomarkers involved in AD. The mRNA expression dataset, GSE28146, containing 15 sample data comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Investigating the range of varying gene expression levels through mass spectrometry analysis, we have identified several genes which were commonly altered at all time points after α-syn PFF injection, including TPPP3 and RAB10, which were upregulated, and CAMK2A and DYNLL1, which were downregulated. These results agree with prior reports on neurodegenerative diseases, where all four genes displaying association with not only Parkinson’s (Simunovic et al, 2009; Zhang et al, 2014; Olah et al, 2020; Fellgett et al, 2021), but also with Alzheimer’s (Kong et al, 2009; Ghosh and Giese, 2015; Ridge et al, 2017; Singh et al, 2022) disease. Thus, while we may conclude that these genes may serve as potential biomarkers for early detection of general neurodegeneration, it appears difficult to assign them to a particular diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Investigating the range of varying gene expression levels through mass spectrometry analysis, we have identified several genes which were commonly altered at all time points after α-syn PFF injection, including TPPP3 and RAB10, which were upregulated, and CAMK2A and DYNLL1, which were downregulated. These results agree with prior reports on neurodegenerative diseases, where all four genes displaying association with not only Parkinson’s (Simunovic et al, 2009; Zhang et al, 2014; Olah et al, 2020; Fellgett et al, 2021), but also with Alzheimer’s (Kong et al, 2009; Ghosh and Giese, 2015; Ridge et al, 2017; Singh et al, 2022) disease. Thus, while we may conclude that these genes may serve as potential biomarkers for early detection of general neurodegeneration, it appears difficult to assign them to a particular diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have been conducted on NGS public sequencing data of AD. Himanshu Narayan Singh used NGS bioinformatics analysis to determine that DYNLL1 and KLRN were significantly associated with AD, which suggested that these proteins may constitute the genetic basis of AD ( 13 ). Furthermore, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses performed by Fang indicated that certain functions, such as taxis and cell-cell signaling, were strongly associated with AD ( 14 ).…”
Section: Introductionmentioning
confidence: 99%